Systemic analysis of urban sustainability indicators: A case study of the city of Moundou, Chad - Haou, Ernest; Tob-Ro, N’Dilbé; Aholou, Cyprien Coffi; Bondoro, Ouya (Edelweiss Applied Science and Technology, 2025)
Contemporary cities are shaped by the intricate interplay of material and immaterial flows operating within non-linear urban metabolisms. In the face of escalating global challenges—most notably climate change and rapid urbanization—their governance has become increasingly complex, exposing the limits of conventional sectoral approaches to urban sustainability decision-making. This complexity is especially pronounced in sub-Saharan African cities, where limited adaptive capacity, financial constraints, and weak governance hinder effective responses to ongoing transformations. In this context, a systemic approach to urban governance offers a compelling framework for strengthening public decision-making. This study applies the MICMAC method (Matrix of Crossed Impacts—Multiplication Applied to a Classification) to identify patterns of influence and dependency among variables. It then uses dynamic systems modeling via Vensim (version 8.2.1) to simulate interactions among twenty interdependent indicators of urban sustainability. The systemic analysis highlighted the strategic relevance of the following indicators: rational land use, accessibility and mobility, urban vegetation density, flood management, and access to health services. Six structuring feedback loops were also identified: the spatial-functional loop, ecological resilience loop, civic cohesion loop, regulatory-economic loop, social inclusion loop, and health–productivity loop. These dynamic interrelations highlight the need for systemically informed urban governance capable of enabling integrated and evidence-based decision-making for sustainable urban development.